2022
DOI: 10.1371/journal.pgen.1010329
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic components are required for glioblastoma progression in Drosophila

Abstract: Glioblastoma (GB) is the most aggressive, lethal and frequent primary brain tumor. It originates from glial cells and is characterized by rapid expansion through infiltration. GB cells interact with the microenvironment and healthy surrounding tissues, mostly neurons and vessels. GB cells project tumor microtubes (TMs) contact with neurons, and exchange signaling molecules related to Wingless/WNT, JNK, Insulin or Neuroligin-3 pathways. This cell to cell communication promotes GB expansion and neurodegeneration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…It acts as a primary calcium (Ca 2+ ) sensor in the mechanisms of neurotransmission and hormone secretion, and it plays a crucial role in processes triggered by Ca 2+ for secretion 28 . Given the involvement of SYT1 and its calcium-binding protein product, this gene has appeared in GBM hub oncogene nodes alongside SV2B 29 , 30 . Moreover, a larger scale analysis of glioblastoma and normal brain tissue samples obtained from the TCGA and GEO databases revealed that SYT1 was one of the core genes associated with GBM progression among the 552 differentially expressed genes in that analysis 31 .…”
Section: Discussionmentioning
confidence: 99%
“…It acts as a primary calcium (Ca 2+ ) sensor in the mechanisms of neurotransmission and hormone secretion, and it plays a crucial role in processes triggered by Ca 2+ for secretion 28 . Given the involvement of SYT1 and its calcium-binding protein product, this gene has appeared in GBM hub oncogene nodes alongside SV2B 29 , 30 . Moreover, a larger scale analysis of glioblastoma and normal brain tissue samples obtained from the TCGA and GEO databases revealed that SYT1 was one of the core genes associated with GBM progression among the 552 differentially expressed genes in that analysis 31 .…”
Section: Discussionmentioning
confidence: 99%
“…A certain number of these underexpressed genes were associated with synaptic signaling. Indeed, recent evidence suggests that gliomas engage in synaptic communication and this neural integration may be crucial for glioma progression [29,30]. It has also been shown that neuron-glioma interactions are bidirectional and gliomas induce hyperexcitability through secretion of synaptogenic factors, and reducing surrounding inhibitory interneurons [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent evidence suggests that gliomas engage in synaptic communication and this neural integration may be crucial for glioma progression [29,30]. It has also been shown that neuron-glioma interactions are bidirectional and gliomas induce hyperexcitability through secretion of synaptogenic factors, and reducing surrounding inhibitory interneurons [30][31][32][33]. Additionally, cell lines' membranome displayed decreased expression of genes related to ion transport and homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…These two models have been widely used to identify new genes and signaling pathways involved in glioma progression. [41][42][43][44][45] Among the genes possibly involved in the progression of glioma, our recent data demonstrated the role of the serotonin 5-HT 7 receptor (5-HT 7 R) in a larval Drosophila model of glioma. 46 The human 5-HT 7 R expression in this animal model reduced larval lethality and partially restored dysregulated biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…The second model, established by Chi et al 40 , allowed to induce glioma development specifically at the adult stage. These two models have been widely used to identify new genes and signaling pathways involved in glioma progression 41–45 …”
Section: Introductionmentioning
confidence: 99%